Composition of Trade in Latin America and the Caribbean - Ding, Xiaodan; Hadzi-Vaskov, Metodij (Washington, D.C. : International Monetary Fund, 2017)
This study analyzes composition of goods trade in Latin America and the Caribbean (LAC) along four main dimensions: revealed comparative advantage, product complexity, sophistication, and diversification. After describing some key trade patterns over the last half century, it compares the findings for LAC with other regions. Second, the study investigates how infrastructure quality, education, and tariff levels affect export composition. Third, using an approach based on product proximity, it aims to predict changes in LAC's future composition of exports. The study concludes that policies to upgrade human capital and infrastructure are essential for increasing LAC's export share in high-skill products.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet